Analysis of Fill Weight, Water Absorption and Density of Plasterboard Ceiling Made of Banana Midrib Fiber - Ana Komariyah; Sisy Anggelina Aulia Aska; Arifa Insani Navalia; Lydia Rohmawati; Woro Setyarsih (Jurnal Ilmu Fisika (JIF), 2021)
The plasterboard ceiling is one of the applications of fiber-based composite materials. Asbestos fibers, usually used to make plasterboard ceilings, are unfortunately harmful to humans. We propose using banana midrib fibers that are environment-friendly to replace asbestos fibers. This research investigates the influence of the percentage of banana midrib fibers on the fill weight, water absorption, and density of plasterboard ceilings. The fibers extracted from banana midrib were immersed in 40 mL of 1 M NaOH and then used to prepare plasterboard ceiling samples with different fiber percentages, namely 0.0%; 1.0%; 1.5%; 2% 2.5%. The fill weight, water absorption, and density of plasterboard samples were measured and then compared to Indonesian National Standard. The highest fill weight of 1.52 g/cm3 was obtained with a 1.0% percentage of banana midrib fibers for the plasterboard sample. In contrast, the highest water absorption of 11.84% was obtained at 2.5% banana midrib fibers. The more fibers added, the better the seepage of the plasterboard ceilings.Â